Pengaruh Pengungkapan Informasi Lingkungan, Sosial, Tata Kelola, Ekonomi, dan Pendekatan Manajemen Terhadap Kebijakan Dividen - Ihsan, Muhammad; Zuraida, Zuraida (Department of Accounting, Faculty of Economics & Business, 2024)
This research aims to determine the influence of Environmental, Social, Governance (ESG) disclosure, Economic disclosure, and Management Approach on Dividend Policy proxied by Dividend Payout Ratio and Dividend Yield. The study incorporates five control variables: company size, age, leverage, profitability, and liquidity. The data used in this research are secondary data obtained from the financial and sustainability reports of companies listed on the Indonesia Stock Exchange in the IDX ESG Leaders Index for the period 2020-2022. The results indicate that the disclosure of environmental, governance, and management information does not have a significant influence on dividend policy, both in terms of Dividend Payout Ratio and Dividend Yield measurements. This finding suggests that environmental, governance, and management disclosures cannot be used as a basis for decision-making for stakeholders. Social disclosure has no significant influence on Dividend Payout Ratio, but it has a significant negative impact on Dividend Yield, indicating that social disclosure affects dividend policy negatively. On the other hand, economic disclosure shows a significant influence on dividend policy, both in terms of Dividend Payout Ratio and Dividend Yield measurements.